2013
DOI: 10.1002/wrcr.20203
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between water color, water levels, and climate indices in large rivers: Case of the St. Lawrence River (Canada)

Abstract: [1] The relationship between the color (measured with Landsat Thematic Mapper and Enhanced Thematic Mapper sensors in bands 1, 2, and 3) of St. Lawrence River (SLR) water and water levels (in SLR and Lake Ontario) was first analyzed, followed by the analysis of the relationship between water levels and four climate indices for the period from 1984 to 2009. Although there is a statistically significant relationship between these first two variables, this link depends on the strength of two factors: the type of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…This correlation is also observed between AMO and annual daily maximum and minimum water levels [12] and for monthly mean water levels [14]. In North America, AMO is correlated negatively to precipitation and streamflow in a large part of the regions located within the continent (e.g., [39][40][41][42]).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…This correlation is also observed between AMO and annual daily maximum and minimum water levels [12] and for monthly mean water levels [14]. In North America, AMO is correlated negatively to precipitation and streamflow in a large part of the regions located within the continent (e.g., [39][40][41][42]).…”
Section: Discussionmentioning
confidence: 55%
“…No study looking at the temporal variability of water levels or streamflow in the St. Lawrence River has addressed this question specifically (e.g., [12][13][14][15][16]). Moreover, these studies have not identified any impact of such hydroclimatic changes on the variability of water levels or streamflow in the St. Lawrence River.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have analyzed the physicochemical and biological characteristics of these waters (e.g., [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]) and of related sediments [25][26][27][28], while other studies focused on optical characterization of these waters (e.g., [27][28][29][30][31][32]). Most of these studies analyzed the spatial variability of these characteristics in the St. Lawrence River, but very few looked at their seasonal and interannual variability.…”
Section: Introductionmentioning
confidence: 99%